Navigating E-Commerce Amidst a Pandemic: Insights from COVID-19 Literature - Dewi, Citra Surya; Mediawati, Noor Fatimah; Khumairoh, Bulqis (Proceedings of The ICECRS, 2023)
This study presents a meticulously curated dataset comprising 1,786 journal articles and conference proceedings sourced from the Lens.org platform, exploring the intersection of E-Commerce and Covid-19 in the realm of Online Business Law. Employing keyword searches, the dataset's significance lies in expediting investigations into the legal dimensions of this nexus, facilitating further research endeavors. The dataset, available in SVC and BibTex formats via Zenodo.org with a DOI link, offers vital insights for scholars delving into the evolving field of E-commerce and Covid-19, enabling a deeper understanding of this critical area of study.Highlights : Comprehensive dataset of 1,786 documents expedites legal investigations into E-commerce and Covid-19. Available in SVC and BibTex formats via Zenodo.org for easy access and reuse. Enables scholars to deepen their understanding of the evolving intersection between E-commerce and Covid-19 from a legal standpoint. Keywords: E-Commerce, COVID-19, Consumer Behavior, Online Market Dynamics, Pandemic Impact